Development of an Embedded Smart Home System - Perumal, Thinagaran (2006)
Smart home systems are expected to become key research area for ubiquitous and embedded system computing in coming years. In this thesis, a new scheme in smart home systems technology using embedded system for providing intelligent control of home appliances is proposed. An embedded system act as protocol glue that incorporates wired and wireless option such as Short Message Service (SMS) router with wireless local area network (WI-FI) for intelligent automation and higher speed of home appliances connectivity. The system is implemented in 2 tier models. First-tier model consist of incorporated design of SMS Router and Wireless Access Point. Wireless local area network (WI-FI) is selected as mechanism due to its transmission range within 100m which suits the smart home requirement for automation and control, justifies the Personal Area Network (PAN) for mobile device connectivity. Second tier model consist of remote application server systems, which cater a conceptual model between embedded hardware and software integration of appliances in smart home. This interface model will be between in house networks and external communication environment, whereas embedded system acts as storage media and server for information interchange between systems especially with mobile devices within a smart home. Embedded system sits at the core of the home network, acts as residential gateway and enables bi-directional communication and data transfer channel among networked appliances in the home and across the Internet. On the other hand, client-side application provides a user-friendly Graphic User Interface (GUI) to enhance the usability of the system. The proposed embedded system has been implemented and verified that the system can be a core device for smart home environment functionality.